What were they all about: Two questions that provoked different reaction and feeling - BOTHA, E MATHAKGA (South African Journal of Higher Education, 2016)
The poor education and lack of exposure to literature for most Blacks in South Africa makes it difficult for second language speakers of English to cope with demanding expectations for engaging with the level of knowledge and skills required for working in higher education (HE). Being black, and being a second language speaker of English and having to work in HE institution, which privileges the use of English have combined to shape my identity in many ways. The theoretical framework of agency and ownership is used in this narrative to share episodes of my journey as a student and academic. Perseverance and persistence enabled me overcome challenges during my studies and to navigate expectations in my academic career. The narrative is based on two questions, the one triggered action of agency, and the other evoked feelings of self doubt and judgement. As a Black woman and second language speaker, the paper intends to share the experiences associated with overcoming these challenges and celebrating success despite all.